Crossover between macroscopic and mesoscopic regimes of vortex interactions in type-II superconductors - Zadorosny, Rafael [UNESP]; Sardella, Edson [UNESP]; Malvezzi, André Luiz [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Ortiz, Wilson Aires (American Physical Society (APS), 2012)
In the present work we report the existence of a crossover between the macroscopic and mesoscopic regimes of vortex interactions in type-II superconductors. Our findings rely on a systematic procedure to determine this crossover, which is based on the influence of the surface on the vortex structure of small superconductors. An adjacent result that we have found is that near this regime transformation, the vortex lattice develops a progressive change of symmetry, from square to hexagonal, which is intimately related to the meso-to-macro crossover. Our numerical simulations have been done for a long superconducting cylinder of square cross section for a wide range of length scales and temperatures. © 2012 American Physical Society.